Management , Capital and Legal Protection of Micro Businesses , Small Medium Enterprises and Small Traders in Suriname - Prayekti Prayekti; Mokhamad Arwani; Dimas Yudhistira; Tri Hadi Sulistyanto; Farida Arianti (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2025)
Purpose The purpose of activity This is For give information about importance management business micro , small and medium enterprises (MSMEs) in general effective . Activities this also aims For convey importance utilization technology in development of MSMEs, providing outlook related certainty relevant policies and laws with MSME businesses , as well as give understanding regarding promotional strategies MSME products so that they can compete in a bigger market wide .Methods – Methods used in implementation Community service through Zoom application and provide counseling to MSMEs from Indonesia, Malaysia, and Suriname. Abdimas Team give Exposure material about introduction plan business .Results and discussions - Activities devotion public international This succeed involving 154 participants from Indonesia, Malaysia, and Suriname. Activities This reach wide audience and discuss management of MSMEs comprehensive , covering planning business , marketing strategy based on collaboration , entrepreneurship , and utilization technology For expand the market.Conclusion Success activity This show importance mentoring sustainable and training deep For answer need specific every sector business . With step this , UMKM can grow in a way sustainable and provide impact more positive wide for ecosystem global business .